Edward Said’s Conception of the Intellectual Resistance - Ahmad Faysal, Yasif; Rahman, Md. Sadequr (American Journal of Humanities and Social Sciences, 2013)
<!–[if gte mso 9]> <![endif]–> This paper attempts to focus on the Saidian intellectual who plays an exemplary role in resisting the ideological misrepresentation that a dominant culture performs over the weak one, which eventually leads to imperialism and colonialism. This resistance is a highly intellectual one and bound with some critical practices on the part of the intellectual himself. Essentially non-coercive in nature, the resistance entails a mode of criticism from him, which is secular in being opposed to dogmatic obsession, amateurist in being free from the traps of professionalism, exilic in having pluralistic viewpoints. The task of resistance also requires an intellectual as critic to consider a cultural artifact like a novel as product of worldly circumstances, which is deeply inflected with the ideological position of the author himself. This, correspondingly, requires a critic to switch from filiative criticism, that texts are traditionally homogenized, to the affiliative one, that they bear the determining imprints of hegemonic influences of cultures, often imperialistic ones. Benefitting from all these insights, an intellectual can participate in a cultural and specifically literary mode of resistance by producing counter- discourse that he terms voyage-in. Eventually, these practices generates a moral courage for a critic and enables him to speak truth to power in all its forms and manifestation. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>